Lack of cooperation between physicians and dentists during osteoporosis treatment may increase fractures and osteonecrosis of the jaw. (2nd July 2016) - Taguchi, Akira; Shiraki, Masataka; Sugimoto, Toshitsugu; Ohta, Hiroaki; Soen, Satoshi; ,
Abstract: Objective: Our previous questionnaire-based survey suggested that discontinuation of antiresorptive agents before tooth extraction may increase adverse events and disturb osteoporosis treatment without completely preventing osteonecrosis of the jaw (O.N.J.). We also found little cooperation between physicians and dentists in Japan. However, limitations of our previous study included a survey of doctors belonging to small clinics and a small sample size. Our current study aimed to confirm the results of our previous survey in doctors mainly belonging to academia. Methods: A structured questionnaire including 14 key clinical queries was sent to 1812 physicians of the Japan Osteoporosis Society, and 629 responses were received. Results: Dentists requested discontinuation of many medications that were not associated with the incidence of O.N.J. A total of 523 respondents had received discontinuation requests from dentists. Of these, 97 respondents experienced 119 adverse events including 25 fractures and seven incidences of O.N.J. The ratios of valid responses for fractures were 3.6% and 5.3% in patients with a discontinuation of <3 and ≥3 months, respectively. Those for O.N.J. were 0.7% and 1.6%, respectively. Respondents who refused discontinuation requests reported no cases of O.N.J. Approximately 17% of respondents had patients who discontinued osteoporosis treatment following a requested drug discontinuation after tooth extraction. Approximately 62% of respondents did not request oral health care by a dentist before antiresorptive therapy, and 72% reported no cooperation between physicians and dentists in their region. Conclusions: This study reconfirms the results of our previous survey. Discontinuation of antiresorptive treatment may increase both fractures and O.N.J. Immediate development of a strategy for sharing information about O.N.J. among physicians, dentists, and patients is required to reduce the incidence of both O.N.J. and skeletal events in osteoporosis treatment. Study limitations were selection bias due to low response rate and possible inaccurate responses to the questionnaire.